PWE-076 Absence Of Gut Microbiota Reduces Lipopolysaccharide-induced Epithelial Cell Shedding In The Small Intestine. (9th June 2014) - Hughes, K; Alcon-Giner, C; Lawson, M; McCoy, K; Macpherson, A; Hall, L; Watson, A
Abstract : Introduction: Cell shedding, the process by which intestinal epithelial cells (IECs) are extruded from the small intestinal (SI) villus, is known to be elevated in patients with inflammatory bowel disease (IBD) and is correlated with disease relapse. Importantly, the epithelial barrier is in contact with intestinal bacterial communities (i.e. the microbiota) and studies have correlated disturbances in the microbiota with IBD. Thus, we hypothesised that cell shedding may be modulated by the microbiota. Methods: Specific pathogen free (SPF) and germ-free (GF) C57BL/6 mice, including GF mice reconstituted for 4 weeks with altered Schaedler flora (ASF), stable Defined Moderately Diverse Microbiota (sDMDMm2), or SPF faeces, were given 10mg/kg Lipopolysaccharide (LPS) intraperitioneally to induce SI cell shedding. Animals were euthanized 1.5 h post-LPS. Tumour Necrosis Factor-α (TNF-α) and cleaved caspase 3 (CC3) ELISA were performed on whole SI homogenates. Immunohistochemistry (IHC) for CC3 was performed on formalin fixed paraffin embedded SI tissue and CC3 +ve villus IECs quantified using WinCrypts and Score programs. Statistics were performed using ANOVA with Dunnett's post-test. Results: ELISA analysis showed significant decreases in CC3 in GF vs SPF mice following LPS administration (2.6-fold+/-0.3, p < 0.01). Decreased levels of TNF-α (GF, 189+/-56 pg/ml vs SPF, 548+/-66; p < 0.01), showed a potential mechanistic basis for this change. Reconstitution with ASF or sDMDMm2 failed to restore levels of shedding observed in LPS treated SPF mice. CC3 ELISA (ASF, 1.1-fold+/-0.3, ns; sDMDMm2, 1.0-fold+/-0.1, ns); TNF-α ELISA (ASF, 311+/-48 pg/ml, p > 0.05; sDMDMm2; 231+/-77 pg/ml, p < 0.05). IHC and count analysis confirmed that LPS treated GF, ASF or sDMDMm2 mice were unable to mount a normal cell shedding response vs LPS treated SPF mice: Mean% CC3 positive IECs along the length of the villus of 4.3%+/-1.2, 0.6%+/-0.3, 0.5%+/-0.2 vs 7.9%+/-1.1, respectively (all p < 0.01). Importantly, when LPS was delivered to GF mice reconstituted with SPF faeces, similar rates of shedding to LPS treated SPF mice were observed and TNF-α production was restored. Conclusion: GF mice are largely refractory to LPS induced cell shedding, when compared to SPF or fully reconstituted GF mice, via modulation of the pro-inflammatory cytokine TNF-α. These data strongly implicate the intestinal microbiota in cell shedding and may help to shape microbiota-based treatment of IBD patients. Disclosure of Interest: None Declared.